Stosowanie unijnych przepisów o transgranicznych zagrożeniach dla zdrowia a ochrona danych osobowych w UE - Dąbrowska-Kłosińska, Patrycja (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
The paper concerns a possible conflict between the scope of data protection of individuals, including their medical data, and the necessity of preparing and reacting to serious cross-border health threats at the EU level, for example, to pandemics. The case-study of Mr Andrew Speaker, who was ordered not to leave the US by the US Centre for Disease Prevention and Control because of his TB infection, but was travelling through Europe in 2007, provides an illustration to problematic legal issues. The text presents EU regulatory tools which aim at preventing the spread of infectious diseases and other serious cross-border health threats as provided by Decision 1082/2013 and the relevant provisions ensuring data protection of individuals in this context. The objective of the extensive normative analysis of the current regulatory framework is an attempt at assessment whether the current system of EU rules can offer an effective protection of personal data when the provisions on pandemics’ prevention are applied.
Keywords: Unia Europejska; przepisy prawne; transgraniczne zagrożenia; zdrowie; ochrona danych osobowych